2018
DOI: 10.1097/aog.0000000000002746
|View full text |Cite
|
Sign up to set email alerts
|

Salpingectomy During Vaginal Hysterectomy

Abstract: We demonstrate a simple technique to safely perform opportunistic salpingectomy during a vaginal hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…It is crucial to have clear dissection with maximum visualization of the fallopian tube in order to remove the entire length of the fallopian tube from the isthmus to the fimbriae. There are multiple approaches described in recent studies to make salpingectomy easier and safer during vaginal hysterectomy, including the round ligament technique, posterior rotation of the uterus, and performing laparoscopically assisted vaginal hysterectomy (LAVH) instead of total vaginal hysterectomy [14][15][16]. An article in 2018 describes a technique that includes posterior rotation of the uterus during vaginal hysterectomy to remove tubes with reported success in all attempts in over 60 cases [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to have clear dissection with maximum visualization of the fallopian tube in order to remove the entire length of the fallopian tube from the isthmus to the fimbriae. There are multiple approaches described in recent studies to make salpingectomy easier and safer during vaginal hysterectomy, including the round ligament technique, posterior rotation of the uterus, and performing laparoscopically assisted vaginal hysterectomy (LAVH) instead of total vaginal hysterectomy [14][15][16]. An article in 2018 describes a technique that includes posterior rotation of the uterus during vaginal hysterectomy to remove tubes with reported success in all attempts in over 60 cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple approaches described in recent studies to make salpingectomy easier and safer during vaginal hysterectomy, including the round ligament technique, posterior rotation of the uterus, and performing laparoscopically assisted vaginal hysterectomy (LAVH) instead of total vaginal hysterectomy [14][15][16]. An article in 2018 describes a technique that includes posterior rotation of the uterus during vaginal hysterectomy to remove tubes with reported success in all attempts in over 60 cases [15]. A recent study of a cohort with pelvic organ prolapse found a 0% failure rate to perform intended salpingo-oophorectomy in LAVH compared to a 36% failure rate in total vaginal hysterectomy [16].…”
Section: Discussionmentioning
confidence: 99%
“…144 Giraudet et al demonstrated a simple technique to safely perform opportunistic salpingectomy during vaginal hysterectomy and reported success in all attempts (more than 60 cases). 145…”
Section: Current Trendmentioning
confidence: 99%
“…However, which technique damages the blood flow to the ovary is unknown. The most-used method in laparoscopic hysterectomy is bipolar electrocautery [13,19].…”
Section: Introductionmentioning
confidence: 99%